2007
DOI: 10.1002/bit.21452
|View full text |Cite
|
Sign up to set email alerts
|

A novel method of encapsulating and cultivating adherent mammalian cells within collagen microcarriers

Abstract: A novel method of preparing collagen microcarriers was developed and used to entrap adherent cells for cell culturing. This new technique involved seeding of cells in micro gel beads comprised of collagen fibrils dispersed in alginate. The gel beads were washed with phosphate buffered saline (PBS) to remove alginate and the resulting microspheres, about 300-500 microm in diameter, contained evenly distributed collagen fibrils which provided a 3D biomimetic environment for cell growth. The applicability of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Previous studies have shown the proliferation and differentiation of myoblasts (cells lines and primary cells) in collagen matrix (Cheema, Yang et al, 2003;Rhim, Lowell et al, 2007;Wu, Huang et al, 2007). In those studies, cells were allowed to proliferate in GM prior to differentiation.…”
Section: C2c12 Single Cells and Aggregates Exhibit High Levels Of Promentioning
confidence: 99%
“…Previous studies have shown the proliferation and differentiation of myoblasts (cells lines and primary cells) in collagen matrix (Cheema, Yang et al, 2003;Rhim, Lowell et al, 2007;Wu, Huang et al, 2007). In those studies, cells were allowed to proliferate in GM prior to differentiation.…”
Section: C2c12 Single Cells and Aggregates Exhibit High Levels Of Promentioning
confidence: 99%
“…Alginate, a natural polysaccharide isolated from brown seaweed, is the most common used gel for cell encapsulation due to its biocompatibility and stability in vivo (de Vos et al, 2002;Shoichet and Rein, 1996;Wu et al, 2007;Murua et al, 2008). Moreover, alginate has the capacity to protect encapsulated cells against recognition by the immune system (Barminko et al, 2011;Herrero et al, 2007;Kang et al, 2014;Trouche et al, 2010;Zanotti et al, 2013), which will enable the use of allogeneic cells.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to alginates and combinations with chitosan (108) or agarose (109), biomaterials like collagen (110), hyaluronic acid (111) and dextran (112) have also been used. For these applications, the materials should have the ability to form a gel in physiological conditions (temperature, pH and ionic strength).…”
Section: Cell Encapsulation For Drug Deliverymentioning
confidence: 99%